Sleep and wakefulness disturbances in Parkinson's disease: A meta-analysis on prevalence and clinical aspects of REM sleep behavior disorder, excessive daytime sleepiness and insomnia - Maggi, Gianpaolo; Vitale, Carmine; Cerciello, Francesco; Santangelo, Gabriella (Sleep medicine reviews, 2023)
Sleep disorders (SDs) are common non-motor symptoms of Parkinson's disease (PD) with wide variability in their prevalence rates. The etiology of SDs in PD is multifactorial because the degenerative processes underlying the disease and their interaction with drugs and clinical features may promote REM sleep behavior disorder (RBD), excessive daytime sleepiness (EDS) and insomnia. Therefore, we designed a meta-analytic study to provide a reliable estimate of the prevalence and associated clinical and neuropsychiatric aspects of SDs in PD. A systematic literature search was performed up to February 2022. Pooled RBD prevalence was 46%, and its occurrence was associated with older age, lower education, longer disease duration, higher levodopa equivalent daily dose (LEDD), worse motor and autonomic manifestations, poorer quality of life and autonomy, and more severe neuropsychiatric symptoms. The pooled prevalence of EDS was 35% and was associated with older age, longer disease duration, worse motor and autonomic symptoms, higher LEDD, reduced autonomy, and more severe neuropsychiatric symptoms. Insomnia was reported in 44% of PD patients and was related to longer disease duration, higher LEDD, and more severe depression. SDs are associated with a more severe PD clinical phenotype; further studies should explore the pathophysiological mechanisms underlying SDs and develop targeted therapeutic strategies.